IMPACT OF CORPORATE NETWORK COMPETENCES ON THE COMPETITIVENESS OF COMPANIES - Veres, Zoltan; Feher, Katalin; Balogh, Adel (European Scientific Journal, ESJ, 2014)
According to our research companies that have closer connections with their clients, suppliers and research institutes use the latest digital/network tools proactively, their organizational and inter-organizational relations are technology oriented, they are more likely to achieve success in research and development (innovation). Existence and development of network competences have a positive impact on corporate culture, inter-organizational technical co-operation, on openness and integration as well as on further innovations. The research plan envisaged making 30 interviews. In the preparation of the sample, we planned to interview in 80% representatives of companies where either digital innovation or the use of digital networks plays a crucial part in their business profile. The remaining 20% were intended to be made up of manufacturing and service companies. The analysis of the sample monitored the way companies and organizations allocated supplementary resources on behalf of information management in order to develop competences and to implement digital innovations. From the results - as suppositions for a future quantitative survey to test - we can state the followings: Using digital network solutions for the purposes of networking is mostly typical of large B2C enterprises, or firms and organizations where the development of (natural) networks plays a crucial part in their business profile (non-governmental organizations). The staff of companies with a “digital profile” play a leading role in terms of utilizing informal professional communities and networks (both online and offline). This mostly involves professional communities, professional platforms and meetings.